‘Laugh a defiance, Laugh in hope’: Suffrage Comedy and Humour as Political Protest - Eleanor Stewart (Cahiers Victoriens et Edouardiens)
In the context of the women’s movement at the turn of the 20th century and the campaign for the vote, the Actresses’ Franchise League produced and performed a body of plays known as « suffrage drama », many of which were comedies. Drawing on a selection of these works, this article considers the relationship between the suffragette and humour. It sets out to show how, having been a target for ridicule in the popular press, suffrage dramatists turn the tables on their opponents. Mirroring the camaraderie and playful spirit of the movement itself, laughter becomes a powerful political tool on the stage. Within the ritualized framework of the comic genre, the suffrage dramatists use self-derision to provoke empathy and encourage derisory laughter towards their detractors. Caricature, satire and farce are all strategies deployed to undermine the ‘antis’ and expose their political stance as hypocritical and incoherent. Whilst hostile anti-suffragist discourse accused feminists of lacking a sense of humour, the comedies portray the resolutely cheerful and feisty female activists as agents of humour. By doing so, the playwrights overturn stereotypes and challenge the conventional gender power dynamics of a patriarchal society in which men dictated laughter. The attention and praise the comedies attracted in not only the suffragist but also the national press suggest that the comic form enabled the dramatists to present a future of female empowerment as logical and inevitable but in a non-confrontational manner.